Peter in the Gospel of John the making of an authentic disciple - Blaine, Brad 1960- (Leiden [u.a.] Brill, 2007)
Introduction -- Peter's call, naming, and confession -- The footwashing, the prediction of the denials, and Peter's promise to follow Jesus -- Swordplay and denials -- The race to the empty tomb -- John 21 as gospel supplement -- The fishing expedition and the miraculous catch of fish -- Shepherd and martyr -- Conclusion
Introduction -- Peter's call, naming, and confession -- The footwashing, the prediction of the denials, and Peter's promise to follow Jesus -- Swordplay and denials -- The race to the empty tomb -- John 21 as gospel supplement -- The fishing expedition and the miraculous catch of fish -- Shepherd and martyr -- Conclusion
Zugl.: Oxford, Univ., Diss., 2007
Archivierung prüfen
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Peter -- the Apostle, Saint; Bible -- Criticism, interpretation, etc; Hochschulschrift